2021
DOI: 10.1039/d1ra03096e
|View full text |Cite
|
Sign up to set email alerts
|

New dinuclear zinc(ii) complexes with Schiff bases obtained from o-phenylenediamine and their application as fluorescent materials in spin coating deposition

Abstract: Tin fluorescent materials were obtained using a spin coating method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…This feature is important, because the tailored emission can lead to potential applications as optical sensors. Similar behavior was noted for the ligands obtained also from o-phenylenediamine [ 30 ].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This feature is important, because the tailored emission can lead to potential applications as optical sensors. Similar behavior was noted for the ligands obtained also from o-phenylenediamine [ 30 ].…”
Section: Resultssupporting
confidence: 81%
“…They are connected with π→π*, IL charge transfer transitions in the azomethine, -NH-CH 2 - bonds and aromatic rings. In comparison with the solutions spectra, the bathochromic shift of the absorption bands (250, 344, 482, 506 nm) in the solid state like it was previously observed by us [ 30 ]. It is connected with the highest rigidity of the molecular skeleton of the cyclic molecule.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…, MeCN and methanol, providing information about the nature of the transitions and charge transfer capabilities of the synthesized compounds. 54 The characteristic π–π* transition in –CN– was recorded. The value of the absorption is shifted bathochromically when the solvent polarity increases.…”
Section: Resultsmentioning
confidence: 99%
“…Binuclear complexes may present in the same or two different metals and are often more interesting than the mononuclear variants in chemical and biological studies. Binuclear complexes with SBs have been widely studied as catalysts [ 79 , 80 , 81 ], in fluorescence and luminescence studies [ 82 , 83 ], and also antimicrobial activities were reported [ 84 , 85 ]. More recently, binuclear complexes with SBs have been suggested for the therapy of COVID-19 disease [ 86 ] on the basis of molecular modeling studies [ 87 ].…”
Section: Binuclear Sbs Complexesmentioning
confidence: 99%